Evolving Workplace Priorities: A Study on Gen Z’s Core Values - Roy, Moumita; Das, Sulagna; Majumder, Tanmoy; Ray, Nilanjan (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The 21st-century workplace is undergoing a profound transformation catalyzed by the entry of Generation Z—individuals born between 1997 and 2012—into the global workforce. This generational shift represents more than a demographic transition; it signifies a redefinition of workplace values, behaviors, and expectations. Gen Z, as true digital natives, bring a deep familiarity with technology, a strong sense of social and environmental responsibility, and a desire for transparency, inclusion, and purpose in their professional lives. Unlike previous generations, they prioritize psychological safety, meaningful work, flexible working conditions, and authentic organizational alignment with their personal values. As a result, employers are increasingly challenged to reimagine traditional human resource practices, leadership approaches, and organizational design. Hierarchical structures, rigid schedules, and authoritative leadership styles are being replaced by collaborative, agile, and human-centered models that resonate more with Gen Z’s preferences. This study explores the strategic implications of these evolving priorities, offering insights for HR professionals, business leaders, and policymakers on how to attract, engage, and retain Gen Z talent. Drawing on contemporary research and global trends, it underscores the need for organizations to foster cultures of empathy, co-creation, continuous learning, and social impact.